PENGARUH BERMAIN MONOPOLI HURUF TERHADAP KEMAMPUAN BERBICARA ANAK USIA 5-6 TAHUN DI TK TELKOM MAKASSAR - Jauhari, Ulmi; Herlina, Herlina; Asti, Andi Sri Wahyuni (Prodi PGMI STIT Sunan Giri Bima, 2023)
The aim of this research is to determine the impact of playing letter monopoly on the speaking abilities of children aged 5-6 years at Telkom Kindergarten Makassar. The approach in this research uses a quantitative approach with a Quasi Experimental Design research type. This study took 12 children as samples, with details of 6 children each in the experimental group and the control group. Wilcoxon Sign Rank test and descriptive statistical analysis were used to analyze the collected data. The results showed that the speaking ability of children in the experimental group who were treated with playing letter monopoly was better than the control group. According to data analysis, it shows that the experimental group experienced an average increase of 24.8, and the control group experienced an average increase of 14.5. According to the results of the Wilcoxon Sig test. (2-tailed) 0.027 < 0.05 so H0 is rejected and H1 is accepted. Therefore, it was concluded that playing letter monopoly had a significant effect on the speaking ability of children aged 5-6 years at Telkom Kindergarten Makassar.